Etika Berbahasa Generasi Z di Platform 'X' - Alya Putri Nur’Aini; Neta Artika Devi; Silvia Eka Maharani Putri; Angela Primakusuma W; Nasywa Shafira Ramadhani; Dewi Puspa Arum (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This research aims to examine the evolving dynamics of language ethics among Generation Z, focusing on their communication behaviors on the